Risk of End-Stage Kidney Disease in Individuals with Diabetes Living Alone: A Large-Scale Population-Based Study - Kyunghun Sung; Jae-Seung Yun; Bongseong Kim; Hun-Sung Kim; Jae-Hyoung Cho; Yong-Moon Mark Park; Kyungdo Han; Seung-Hwan Lee (Diabetes & Metabolism Journal, 2025)
Background Previous research has linked solitary living to various adverse health outcomes, but its association with diabetic complications among individuals with type 2 diabetes mellitus (T2DM) remains underexplored. We examined the risk of endstage kidney disease (ESKD) in individuals with diabetes living alone (IDLA). Methods This population-based cohort study used the National Health Information Database of Korea, which included 2,432,613 adults with T2DM. Household status was determined based on the number of registered family members. IDLA was defined as continuously living alone for 5 years or more. A multivariable Cox proportional hazards model was used to evaluate the association between living alone and the risk of developing ESKD. Results During a median follow-up of 6.0 years, 26,691 participants developed ESKD, with a higher incidence observed in the IDLA group than in the non-IDLA group. After adjusting for confounding variables, the hazard ratio for ESKD in the IDLA group was 1.10 (95% confidence interval, 1.06 to 1.14). The risk of ESKD was particularly elevated in younger individuals, those without underlying chronic kidney disease, with longer durations of living alone, and with low household income. Adherence to favorable lifestyle behaviors (no smoking, no alcohol consumption, and engaging in regular exercise) was associated with a significantly lower risk of ESKD, with a more pronounced effect in the IDLA group. Conclusion Living alone was associated with a higher risk of ESKD in individuals with T2DM. Tailored medical interventions and social support for IDLA are crucial for the prevention of diabetic complications.